2018
DOI: 10.1038/s41366-018-0011-7
|View full text |Cite
|
Sign up to set email alerts
|

GQ-11: A new PPAR agonist improves obesity-induced metabolic alterations in LDLr−/− mice

Abstract: GQ-11 is a partial/dual PPARα/γ agonist that demonstrates anti-diabetic effects. Additionally, it improves the lipid profile and ameliorates chronic inflammation associated with obesity in atherosclerosis-prone mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Consistently, previous studies also showed anti-inflammatory effects promoted by GQ-11, through TNF-α, CCL-2 and IL-1β modulation in obese mice (SILVA et al, 2018). Evidences suggest that IL-1β plays a key role in pathophysiology of hepatic I/R injury, some of them attesting that neutrophils and macrophages can contribute to the cytokine maturation, independently of inflammasome (SADATOMO et al, 2017).…”
Section: Ischemia/reperfusion (Ir) Inflammation and Oxidative Stresssupporting
confidence: 68%
“…Consistently, previous studies also showed anti-inflammatory effects promoted by GQ-11, through TNF-α, CCL-2 and IL-1β modulation in obese mice (SILVA et al, 2018). Evidences suggest that IL-1β plays a key role in pathophysiology of hepatic I/R injury, some of them attesting that neutrophils and macrophages can contribute to the cytokine maturation, independently of inflammasome (SADATOMO et al, 2017).…”
Section: Ischemia/reperfusion (Ir) Inflammation and Oxidative Stresssupporting
confidence: 68%
“…Our previous studies indicated beneficial properties of a novel PPAR agonist (GQ-11) that may represent a promising candidate for the therapy of diabetes complications. 15 In this study, our major findings are that GQ-11 induces a pro-healing phenotype both in cultured macrophages and when applied topically to wounds of diabetic mice, which resulted in accelerated re-epithelization and collagen deposition.…”
Section: Discussionmentioning
confidence: 84%
“…GQ-11 is a new thiazolidine compound, exhibiting partial/dual PPARa/c agonism with classical antidiabetic effects of TZDs, improves lipid profile and reduces chronic inflammation associated with obesity in mice with reduced side effects. 15 Therefore, the aim of this study was to determine whether GQ-11 reduces inflammation and improves wound healing in diabetic mice in basic research, providing better understanding of underlying mechanisms, improving diabetic wound healing clinical trials and purposing a new approach to diabetic wound healing treatment to prevent its complications such as amputations.…”
Section: Clinical Problem Addressedmentioning
confidence: 99%
See 2 more Smart Citations